Problem based learning with geogebra software on self confidence of junior high school students - Marlina, Ratna (CV. Pustaka Literasi Ilmiah, 2023)
This research is motivated by the low level of confidence of junior high school students, so it is necessary to design learning that overcomes these problems. One of the alternative solutions is using problem-based learning approach with the help of GeoGebra software. In the process, this research uses an experimental design, where there is an experimental class that uses a problem-based learning approach and a control class using the usual approach. The population in this study were junior high school students in Cimahi city while the sample was in one of the junior high schools in Cimahi city. Data collection techniques using non-test instruments in the form of self-confidence questionnaire as many as 25 questions. Data processing techniques using two mean difference test. The results showed a significant 0.490 > 0.05. which means that there is no difference in mathematical self-confidence of junior high school students using a problem-based learning approach assisted by geogebra with those who learn using ordinary learning. This happens because of several factors such as time and learning environment that is less conducive, the use of methods, students such as lack of enthusiasm and concentration.